In-situ electrochemical ESR: First-order kinetics and transient signals - Compton, R; Page, D; Sealy, G (1984)
Unstable radicals may be generated at a channel electrode positioned at the centre of an ESR cavity. Theory is given describing the transient ESR signals associated with the growth or the decay of the electrogenerated radical when the current at the electrode is stepped. In particular when the radical decomposes by first-order kinetics the transients can be related to the rate constant, the solution flow rate and the electrode geometry. Experiments with the semifluorescein radical and with the 2-nitropropane radical anion are shown to be in excellent agreement with theory.